ENHANCING STUDENTS’ HIGHER ORDER THINKING SKILL THROUGH GUIDING QUESTION TECHNIQUE - Eneng Rohanah,; Ruminda,; Lidwina Sri Ardiasih, (ENGLISH JOURNAL, 2025)
This study examined the effectiveness of the guiding question technique in enhancing students’ Higher-Order Thinking Skills (HOTS) at a senior high school in Cianjur. It employed a quantitative approach with an experimental design, using pre- and post-tests to assess HOTS development. The findings revealed that in the control class, the mean HOTS score before treatment was 61.88, which increased to 74.00 after applying the conventional method. The significance value for the HOTS assessment variable in this group was 0.840. Meanwhile, in the experimental class, the mean HOTS score before treatment was 61.38, rising to 88.62 after implementing the guiding question technique. The post-test HOTS assessment in this group showed a significance value of 0.000. The t-test results confirmed a significant difference between the experimental and control groups, indicating that students in the experimental class achieved a higher improvement in HOTS compared to those in the control class. These results establish that the guiding question technique is an effective method for enhancing students' higher-order thinking skills.